(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Based on the analysis of the processes of conception, production and realization of the scenario of the play Baile, a graduation production for the students of the Teatro Universitário da UFMG, directed by Thálita Motta, this article intends to discuss how the scenography and the forms of space appropriation collaborate with the different ways of promoting the engagement of the reception in the artistic work, increasing the possibilities of relationship between the scene and the public. As a theoretical contribution, the contemporary discussion on Immersive Theater is mobilized, a way of proposing contemporary theater based on the production of experiences, as well as some previous staging proposals guided by the investigation of spatialities as relevant devices for visuality from the scene.